Influence of Work Pace on Upper Extremity Kinematics and Muscle Activity in a Short-Cycle Repetitive Pick-and-Place Task - Luger, T.; Mathiassen, Svend; Srinivasan, D.; Bosch, T. (2017)
© The Author 2017. Published by Oxford University Press on behalf of the British Occupational Hygiene Society. Objectives: This study investigated the extent to which controlled changes in work pace in a cyclic pick-and-place task influence upper extremity kinematics and muscle activity, and whether an effect depends on working height.Methods: Thirteen participants performed the task for 4 min at each of five work paces ranging from 8 to 12 cycles·min-1 in each of two experimental conditions where the hand was moved horizontally with an average upper arm elevation of 30° and 50°, respectively. For each work cycle, we calculated the average and standard deviation of the upper arm elevation angle and the activity of the trapezius and deltoid muscles, as well as the angular peak velocity. We summarized these seven variables by calculating averages across cycles and cycle-to-cycle variabilities.Results: At 30° arm elevation, pace significantly influenced within-cycle angle variation, cycle-to-cycle variability of the average angle, angular peak velocity, and cycle-to-cycle variability of peak velocity. However, only angular peak velocity increased monotonically across all paces from 8 to 12 cycles·min-1). Average activity in the trapezius and the deltoid were the only muscle activity variables to increase consistently with pace. These effects of work pace did not change with working height.Conclusion: The present study did not find any consistent work pace effect on upper extremity kinematics and muscle activity, in spite of a comprehensive empirical basis compared to previous literature. While our results suggest that work pace may not be of critical concern in an occupational health context, we encourage further studies verifying or disproving this notion.